Temporal evolution of beta bursts in the parkinsonian cortical and basal ganglia network - Cagnan, H; Mallet, N; Moll, C; Gulberti, A; Holt, A; Westphal, M; Gerloff, C; Engel, A; Hamel, W; Magill, P; Brown, P; Sharott, A (National Academy of Sciences, 2019)
Prevalence and temporal dynamics of transient oscillations in the beta frequency band (15 to 35 Hz), referred to as β bursts, are correlated with motor performance. Disturbance of these activities is a candidate mechanism for motor impairment in Parkinson’s disease (PD), where the excessively long bursts correlate with symptom severity and are reduced by pharmacological and surgical treatments. Here we describe the changes in action potential firing that take place across multiple nodes of the cortical and basal ganglia circuit as these transient oscillations evolve. These analyses provide fresh insights into the network dynamics of β bursts that can guide novel strategies to interfere with their generation and maintenance in PD.